Semiconducting properties of some u-bridged phthalocyanines - Hussein, Nazar A. (1990)
The application of organic materials in electronic devices depends, in part, on the ability to control the electrical properties by structural modification. This thesis explores the possibility of modifyng the properties in the cofacially stacked polymeric phthalocyanine, fluoroaluminium phthalocyanine (AIPcF) by copolymerisation with the structurally related fluorogallium phthalocyanine (GaPcF).